Inside Back Cover: Singlet Oxygen during Cycling of the Aprotic Sodium–O2 Battery (Angew. Chem. Int. Ed. 49/2017). Issue 49 (13th November 2017) - Schafzahl, Lukas; Mahne, Nika; Schafzahl, Bettina; Wilkening, Martin; Slugovc, Christian; Borisov, Sergey M.; Freunberger, Stefan A.
Abstract : The biggest hurdle facing the development of Na–O2 batteries is parasitic chemistry. In their Communication onpage 15728  ff., S. A. Freunberger et al. show evidence that the highly reactive singlet oxygen forms at all stages of cycling, especially at high charging voltages, and that it is the main driver for parasitic reactions. However, trace water, which is needed for high capacities, also drives the parasitic chemistry. Ways to prevent or eliminate singlet oxygen are, therefore, needed to improve cyclability.